ORIENTALIST CRITICISM TO QIRA’AT MUTAWATIRAH AND DEFENSE (A FACT AND REALITY) - Mohd Faizulamri bin Mohd Saad; Afrizal Nur (Jurnal Ushuluddin, 2016)
Qira’at mutawatirah is the word of Allah. It is the source and the most important element in the studying al-Qur’an. It is a primary reference source, in its capacity as al-Qur’an revealed by Allah SWT. But the problem that arises is when some scientists and orientalists attempt to criticize Qira’at mutawatirah and embroider it with misconceptions. This condition becomes worse, because it was found from critical that refused accuracy of Qira’at mutawatirah by concluding Qira’at mutawatirah is wrong. Based on the statement above, this paper will discuss and analyze about the views that criticize Qira’at mutawatirah to explain the reasoning-defense argument. This study is a qualitative research and focused on documents analysis. The findings of this study concluded that the arguments defense Qira’at mutawatirah is a strong argument, while criticism argued is not correct, because their consideration simply put human logic of the word of Allah SWT